Optimalisasi Fungsi Manajemen Keperawatan dalam Implementasi Jenjang Karir dan Kredensialing pada Staf Keperawatan - Halimatul Nurhikmah; Rr. Tutik Sri Hariyati; Andi Amalia Wildani; Nurhayati Nurhayati (Journal of Telenursing (JOTING), 2023)
This study aims to identify problems, develop innovation strategies for problem-solving, implement problem-solving innovation strategies, evaluate the implementation of activities, and plan follow-up of the evaluation results related to the performance of career paths and nursing credentials. The method used is a case report which begins with problem identification through interviews, observation, secondary data, and surveys using online questionnaires. The results showed that the credentialing of nursing staff could have been more optimal as a priority problem. The innovation strategy implemented was the preparation of Standard Operating Procedures (SPO) for Planning Implementation of Increasing the Nursing Career Path, nursing career path planning tools based on Google spreadsheets, work instructions for using tools, and educational videos on career paths and nurse credentials. In conclusion, the implementation of career paths and nursing credentials at Hospital X has been going quite well, but it could be optimized in some ways. Strategies to maximize the performance of career paths and nursing credentials in nursing management functions, namely planning, organizing, staffing, actuating, and controlling. The innovation developed by creating a planning tool for implementing nursing career advancement based on data processing software that can be accessed online so that it is poured into a Google spreadsheet. Planning for an increase in the nursing career path carried out by the head of the room can be optimized by involving the implementing nurse. Keywords: Management Function, Nurse Career Path, Credentialing